Additional Common Polymorphisms in the PON Gene Cluster Predict PON1 Activity but Not Vascular Disease. (22nd May 2012) - Kim, Daniel S.; Burt, Amber A.; Ranchalis, Jane E.; Richter, Rebecca J.; Marshall, Julieann K.; Eintracht, Jason F.; Rosenthal, Elisabeth A.; Furlong, Clement E.; Jarvik, Gail P.
Abstract : Background . Paraoxonase 1 (PON1) enzymatic activity has been consistently predictive of cardiovascular disease, while the genotypes at the four functional polymorphisms at PON1 have not. The goal of this study was to identify additional variation at the PON gene cluster that improved prediction of PON1 activity and determine if these variants predict carotid artery disease (CAAD). Methods . We considered 1, 328 males in a CAAD cohort. 51 tagging single-nucleotide polymorphisms (tag SNPs) across the PON cluster were evaluated to determine their effects on PON1 activity and CAAD status. Results . Six SNPs (four in PON1 and one each in PON2/3 ) predicted PON1 arylesterase (AREase) activity, in addition to the four previously known functional SNPs. In total, the 10 SNPs explained 30.1% of AREase activity, 5% of which was attributable to the six identified predictive SNPs. We replicate rs854567 prediction of 2.3% of AREase variance, the effects of rs3917510, and a PON3 haplotype that includes rs2375005. While AREase activity strongly predicted CAAD, none of the 10 SNPs predicting AREase predicted CAAD. Conclusions . This study identifies new genetic variants that predict additional PON1 AREase activity. Identification of SNPs associated with PON1 activity is required when evaluating the many phenotypes associated with genetic variation near PON1.